The Dynamics of Social Conflict and Multicultural Dialogue in the Era of Globalization - Azis, Irfan (International Journal of Social Research, 2025)
Globalization has increased the intensity of cross-cultural interactions, which on the one hand opens up opportunities for knowledge exchange, but on the other hand also raises potential social conflicts due to differences in identities, economic competition, social gaps, and provocations in digital media. This condition emphasizes the urgency of studying the dynamics of social conflict and multicultural dialogue strategies as relevant resolution mechanisms in the era of globalization. The purpose of this study is to identify the triggering factors of social conflict, analyze the role of multicultural dialogue in reducing inter-identity tensions, and formulate effective strategies in encouraging social cohesion. The method used is a mixed method, with a quantitative approach through a survey of urban multicultural communities (n=200) using a Likert scale questionnaire, and a qualitative approach through in-depth interviews and focus group discussions. Quantitative data analysis was carried out with descriptive and inferential statistics, while qualitative data was analyzed thematically. The results show that differences in cultural identity are the dominant factors triggering conflicts (35%), followed by economic competition (28%), social disparities (21%), and digital media (16%). Qualitative findings show that multicultural dialogue based on the principles of mutual recognition, equal participation, and social justice plays an important role in fostering reconciliation and social cohesion. This research emphasizes that multicultural education policies, cross-cultural festivals, and digital literacy are practical strategies that need to be implemented to strengthen social integration in the era of globalization.